Seeking the threshold effect in self-reference theory : using collectivism to increase distance between real and ideal self-image - Ngan, Hui Hong. (2008)
This research commenced with the intention to seek a threshold effect for collectivists regarding their attitudes towards advertisements as the distance between their self-image and the image projected in an advertisement is accentuated. The experimental process makes use of the individualists and collectivists as two different groups to conduct the analysis.